2005
DOI: 10.1161/01.str.0000190005.09442.ad
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Annular Calcification, Aortic Valve Sclerosis, and Incident Stroke in Adults Free of Clinical Cardiovascular Disease

Abstract: Background and Purpose-Mitral annular calcification (MAC) and aortic valve (AV) sclerosis have each been linked to cardiovascular disease. Whether MAC and AV sclerosis are risk factors for stroke independent of other echocardiographic or laboratory predictors has not been established. We evaluated the relationship between MAC, AV sclerosis, and first stroke events in a population-based cohort. Methods-Our study cohort consisted of 2723 American Indians participating in the Strong Heart Study who were free of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
92
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(97 citation statements)
references
References 43 publications
1
92
0
4
Order By: Relevance
“…We assume that our results may reflect an association between thyroid function and atherosclerotic state in male individuals with high TSH levels, taking into account that AVS and MAC both share common risk factors of atherosclerosis [1,2,4,6], and are highly associated with generalized atherosclerosis [6], coronary artery disease [16,17], myocardial infarction [5], and stroke [4]. In particular MAC is strongly associated with cardiovascular disease [12,18].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We assume that our results may reflect an association between thyroid function and atherosclerotic state in male individuals with high TSH levels, taking into account that AVS and MAC both share common risk factors of atherosclerosis [1,2,4,6], and are highly associated with generalized atherosclerosis [6], coronary artery disease [16,17], myocardial infarction [5], and stroke [4]. In particular MAC is strongly associated with cardiovascular disease [12,18].…”
Section: Discussionmentioning
confidence: 76%
“…Pathohistologically, early lesions represent the summation of degenerative and inflammatory processes that are similar to the development of atherosclerosis, resemble atherosclerotic plaques, and are characterized by lipid and calcium deposition in the valve annular fibrosa [3]. Thus, AVS and MAC are independently associated with atherosclerotic diseases [2,[4][5][6].…”
mentioning
confidence: 99%
“…Our finding of BNP as a risk factor for stroke also has not been reported before. Cardiomyopathy and valvular heart disease can be risk factors for stroke in cardiac diseases (8,17). However, these two were not present in the stroke group.…”
Section: Discussionmentioning
confidence: 87%
“…[1][2][3][4] Remarkably, data on AVC and risk of incident stroke have been less unambiguous. 5,6 Previous populationbased studies demonstrated substantial variations in risk estimates, 1,2,4 with HRs ranging from 1.09 to 1.38.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Interestingly, knowledge on the relation of AVC with subsequent risk of stroke remains uncertain, 5,6 because of limited and conflicting data. Yet, as potential source of cardioembolism 7 and its relatively high prevalence in the general population of ≥60 years, 4,8 further evaluation of AVC in relation with future stroke is warranted.…”
mentioning
confidence: 99%